Determining the conditions for decreasing cutting force and temperature during machining - Nоvikоv Fedir; Polyansky, Vladimir; Shkurupiy, Valentin; Novikov, Dmytro; Hutorov, Andrii; Ponomarenko, Yevhen; Yermolenko Oksana О.; Yermolenko Oleksii А. (Eastern-European Journal of Enterprise Technologies, 2019)
The theoretical approach to calculating and controlling the force and temperature parameters of edge cutting and abrasive machining processes taking into account the provision of the minimum possible power consumption of the cutting process is given. The conditions for reducing cutting force and temperature and improving the quality and rate of grinding and edge cutting machining are theoretically determined. They consist mainly in reducing the relative shear angle of the machined material and, accordingly, power consumption by increasing the cutting capacity of the tool. It is analytically found that in grinding, cutting force and temperature are greater than in edge cutting machining due to the intense friction of the grinding wheel bond with the machined material and the presence of negative rake angles of cutting grains. It is shown that cutting temperature during grinding can be reduced using the multipass grinding pattern, as well as patterns of high-velocity creep-feed wheel-face and double-disc grinding. On this basis, the approach to creating technologies of effective high-velocity defect-free edge cutting and abrasive machining of machine parts and carbide cutting tools is developed. The developed technology of form grinding on the modern HOFLER RAPID 1250 gear grinding machine using a special highly porous form abrasive wheel tapered on both sides received practical application. This wheel has a high cutting capacity in conditions of high-velocity creep-feed grinding. Compared to the conventional method of gear grinding by the generating process, carried out under conditions of multipass grinding, this allowed increasing machining rate up to 5 times. The technology of high-velocity creep-feed external grinding of multipoint carbide cutting tools (milling cutters, reamers) with high-strength metal-bonded diamond wheels using the electrical discharge dressing method is developed. This made it possible to increase the rate by 2–3 times and provide high-quality defect-free machining of carbide tools